A 'Sufi' epistle on spiritual poverty, and its authors: authenticity, authority, and genre in textual reproduction. (5th January 2022) - Kars, Aydogan
Abstract: A range of widely copied Arabic works on asceticism and spiritual poverty attributed to prominent Muslim scholars, Najm al-Dīn al-Kubrā, ʿUmar al-Suhrawardī, Yaḥyā al-Suhrawardī, Athīr al-Dīn al-Abharī, and Aḥmad Zarrūq, are either identical, or contain significant overlaps. This paper analyses the content and reception of this work, and the 36 manuscripts of it available, in order to clarify the issues around its authenticity, authorship, and genre. It makes four key arguments. First, it argues that Minhāj al-sālikīn widely attributed to al-Kubrā is not an authentic work. It is a recent ascription that invents this title and changes the creedal content of an originally longer work. Second, a shorter version of this work can be ascribed to ʿUmar al-Suhrawardī in a particular sense of pre-modern authorship. He compiled a selection from the longer work that was penned by someone else––in the same way his Irshād al-murīdīn is mostly selections from al-Qushayrī's Risāla . Third, different versions of the treatise are mistakenly attributed to Zarrūq, Athīr al-Dīn al-Abharī, and Yaḥyā al-Suhrawardī in various publications and manuscripts. Finally, the original version was penned by one of the less-known teachers of Ibn al-ʿArabī, Abū ʿAmr ʿUthmān al-Abharī, and soon attributed to more celebrated figures. Through these later agents and their attributions, reproductions, redactions, and publications, the text came to be situated within a Sufi framework and genre. Thus, the epistle on poverty exemplifies not only the construction of 'Sufism' as a genre beyond the authorial intention, but also the dispersal of the author-function typical for this genre.